Thermal requirements, fertility life table and biological parameters of Cleruchoides noackae (Hymenoptera: Mymaridae) at different temperatures - Becchi, Luciane Katarine [UNESP]; Barbosa, Leonardo Rodrigues; Serrão, José Eduardo; Zanuncio, José Cola; Sampaio, Marcus Vinicius; Domingues, Maurício Magalhães [UNESP]; Wilcken, Carlos Frederico [UNESP] (PeerJ, 2023)
Cleruchoides noackae Lin & Huber (Hymenoptera: Mymaridae) was imported to Brazil in 2012, to manage the exotic pest Thaumastocoris peregrinus Carpintero & Dellapé (Hemiptera: Thaumastocoridae), which has been damaging eucalyptus plantations. Knowledge of the thermal requirements and the fertility life table of C. noackae is important to improve mass rearing methods for this parasitoid and the effectiveness of its release to manage T. peregrinus. The objective was to evaluate the development period, thermal requirements and the fertility life table of C. noackae at different temperatures. The egg-adult period of this parasitoid varied from 43 to 14 days at 15∘C and 30∘C, respectively. The emergence of C. noackae adults was higher at 15∘C, 18∘C, 21∘C and 24∘C than at 30∘C. Female and male C. noackae need 226.75 and 230.41 degree-days and temperatures higher than 10.06∘C and 9.90∘C, respectively, to complete egg-adult development. The number of parasitized eggs per C. noackae female was higher at 21∘C, 24∘C and 27∘C, with 5.82, 7.73 and 5.50 eggs, respectively, than at 30∘C (0.45). Cleruchoides noackae longevity was greater at 15∘C, 21∘C and 24∘C. The net reproductive rate of the parasitoid was higher at 21∘C and 24∘C than at 30∘C, 3.05, 4.70 and 0.16, respectively. The finite rate of increase of C. noackae was greater at 21∘C, 24∘C and 27∘C, than at 30∘C and the intrinsic rate of increase was negative at 30∘C, −0.100. The temperatures 21∘C and 24∘C and from 18∘C to 27∘C are the most adequate for the reproduction and population increase of C. noackae parasitizing eggs of T. peregrinus, respectively.
Keywords: Biological control; Bronze bug; Degree-Days; Development; Eucalyptus spp; Parasitism